UPAYA PENCEGAHAN PERUNDUNGAN DENGAN MENGGUNAKAN MEDIA BIG BOOK MELALUI KEGIATAN SERVICE LEARNING - Hasanah, Tita; Nurdiani, Siti Nanda; Mukri, Rusdiono (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
The Community Service (PKM) activity carried out aims to prevent bullying among students. The media used is the Big Book with the service learning method. The location of the community service activity is at the Tarbiyatul Falah Al Baenuriyah Private Elementary School, Pamijahan, Bogor Regency. The target of this community service activity is 33 students in grade five. The stages of the activity consist of observation, planning, implementation, and evaluation. The implementation of this PKM activity went well and smoothly and provided several recommendations for further activities..